(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the chemical composition of the valerian plant, studied using HPLC, while the content of important flavonoids was determined experimentally. Based on the results of the studies, it was noted that it was used in folk medicine for the prevention and treatment of neurosthenia (irritability) of diseases of the central nervous system common among the population. In addition, recommendations are given on the use of natural remedies prepared from the root of the plant (together with the rhizome), healing food supplements for insomnia, mental disorders.